EVALUATION OF VARIOUS NATURAL DIETS FOR MASS REARING OF Spodoptera frugiperda J.E SMITH (LEPIDOPTERA: NOCTUIDAE) - Ginting, Sempurna; Sunardi, Tri; Sari, Chaincin Buana; Wibowo, Risky Hadi (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2021)
Evaluation of various natural diets for mass rearing of Spodoptera frugiperda J.E Smith (Lepidoptera: Noctuidae).Spodoptera frugiperda is one of the pests that attack corn in Indonesia. This study aimed to evaluate the most suitable dietfor rearing of S. frugiperda from various natural diets. The study was conducted in vitro. The treatments were consisted ofvariation on S. frugiperda natural diets, such as maize leaf, green mustard leaf, water spinach, sweet potato leaf, sugar caneleaf, and soybeans leaf. The observed variables were life cycle period, pupa size, and pupa weight. The results showed thatthe shortest life cycle period was on corn leaves diet (40.92 days), and the longest was on sugarcane leaves (45.01 days). Thelongest size of pupa were S. frugiperda on mustard leaves diet (12.86 mm) and corn leaves (12.56 mm), The heaviest pupaweights were observed in S. frugiperda on mustard leaves diet (0.18 mg), and corn leaves (0.16 mg). Based on the data, it couldbe concluded that corn leaves were the most suitable type of diet for the growth and development of S. frugiperda.